Ethnic reconciliation after the civil war in Sri Lanka: Can pursuing accountability for war crimes reconcile divided ethnic groups? - Chandran, S. (University of Colombo, 2017)
Reconciliation after a conflict carries positive connotations that suggest an end to antagonism, a graceful acceptance of disappointment or defeat, and a healing and repair of ties of friendships. This is the current necessity for Sri Lanka since the major causes and effects of the prolonged conflict and civil war have provoked negative attitudes among the different ethnic groups. Especially during the last months of the civil war in Sri Lanka, very serious allegations of war crimes and crimes against humanity were made against both parties involved in the final battle by both the United Nations panel of experts and the Lessons Leant and Reconciliation Commission. At the conclusion of the civil war, demands for accountability of the wrongdoers and justice for the victims were high. Though the LTTE was also found to be an offender of alleged war crimes and grave violations of Human Rights, the international community put increased pressure only on the government to ensure accountability. Such moves on the part of the international community have created rifts between ethnic communities and aroused public resentment. This erodes the consensus that needs to be built in the process of reconciliation. The allegations against the government’s armed forces, who are honoured by the Sinhalese for their sacrifices to defeat the LTTE, are deepening the level of anger and humiliation borne by many Sinhalese. This situation will not pave the way to ethnic reconciliation in post-civil war Sri Lanka. In this context, the paper attempts to highlight what transpired during the battle’s final phases and identify the role of the diaspora and the international community. More specifically, it examines how their efforts can trigger negative reactions among the majority Sinhalese and hinder the ongoing ethnic reconciliation process in Sri Lanka. The paper is based on primary and secondary sources of data, and the analysis is based on the three Fs: Facts, Feelings, and Forecasts.
Keywords: war crimes, accountability, reconciliation, ethnic groups